Early detection of dementia through retinal imaging and trustworthy AI - Hao, Jinkui; Kwapong, William R.; Shen, Ting; Fu, Huazhu; Xu, Yanwu; Lu, Qinkang; Liu, Shouyue; Zhang, Jiong; Liu, Yonghuai; Zhao, Yifan; Zheng, Yalin; Frangi, Alejandro F.; et al. (Springer, 2024)
Alzheimer's disease (AD) is a global healthcare challenge lacking a simple and affordable detection method. We propose a novel deep learning framework, Eye-AD, to detect Early-onset Alzheimer's Disease (EOAD) and Mild Cognitive Impairment (MCI) using OCTA images of retinal microvasculature and choriocapillaris. Eye-AD employs a multilevel graph representation to analyze intra- and inter-instance relationships in retinal layers. Using 5751 OCTA images from 1671 participants in a multi-center study, our model demonstrated superior performance in EOAD (internal data: AUC = 0.9355, external data: AUC = 0.9007) and MCI detection (internal data: AUC = 0.8630, external data: AUC = 0.8037). Furthermore, we explored the associations between retinal structural biomarkers in OCTA images and EOAD/MCI, and the results align well with the conclusions drawn from our deep learning interpretability analysis. Our findings provide further evidence that retinal OCTA imaging, coupled with artificial intelligence, will serve as a rapid, noninvasive, and affordable dementia detection.
Keywords: 4203 Health Services and Systems; 42 Health Sciences; Neurodegenerative; Bioengineering; Brain Disorders; Networking and Information Technology R&D (NITRD); Clinical Research; Alzheimer's Disease; Neurosciences; Aging; Dementia; Alzheimer's Disease including Alzheimer's Disease Related Dementias (AD/ADRD); Eye Disease and Disorders of Vision; Machine Learning and Artificial Intelligence; Prevention; Acquired Cognitive Impairment; 4.1 Discovery and preclinical testing of markers and technologies; Eye; Neurological; 4203 Health services and systems